Upgrading Speaking Ability Through Peer Teaching Technique - Hendri Gunawan; Nurbianta Nurbianta (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
This research focus in eighth grade is VIII A and VIII B. the researcher used Peer teaching technique to prove that students taught to use Peer teaching technique better and positively affect students' speaking ability than students taught by using Ordinary way in the eighth grade at SMP 1 Teluk Bayur, the specifics problems discussed in the following formulated questions; (1) What is the students’ performance of pretest and posttest between control and experimental groups?, (2) Is there any significant difference between pretest and posttest performance of the control and experimental groups? This research used Experimental method. This research was conducted from February 22th 2019 to 25th March 2019 in second grade at SMPN 1 Teluk Bayur. The research using Peer teaching technique to improve students’ speaking ability. The Instrument’s research is test, in the test there are Pre-test, treatment and Post-test. Data analysis was scoring, normality, homogeneity, finding mean, and demonstrated T-Test.